Просторовий аналіз структури центральних місць адміністративних районів Волинської області з використанням центрографічного методу - Лажнік, Володимир; Пугач, Сергій; Lazhnik, Volodymyr; Puhach, Sergij (My University, 2017)
Визначено з використанням методів центрографії географічні координати географічних центрів адміністративних районів Волинської області та центрів ваги всього населення районів за даними перепису населення 2001 р. Виявлено ступінь просторової неоднорідності розміщення й концентрації населення адміністративних районів області. Розраховано параметри ексцентральності районних центрів області в низових системах розселення населення й здійснено оцінку взаємного позиційного впливу демографічного й географічного центрів території районів на розміщення райцентрів. The geographic coordinates of geographical centers of Volyn region administrative districts and centers of weight of the total population of districts according to the census data of 2001 were determined using the methods of centography. The degree of spatial heterogeneity of placement and concentration of population in administrative districts of the region is revealed. The parameters of excentrality of district centers of the region in the population settlement systems are calculated and an estimation of the mutual positional influence of the demographic and geographical centers of the districts on the location of district centers was made.
Spatial Analysis of the Structure of Central Places of Volyn Region Administrative Districts Using the Centrographic Method
Keywords: адміністративний район; географічний центр; демографічний центр; коефіцієнт ексцентральності; центрографічний метод; administrative district; geographical center; demographic center; coefficient of excentrality; centrographic method